Telepresence-place-based foreign language learning and its design principles. Issue 3 (4th March 2022) - Liao, Jian; Lu, Xiaofei; Masters, Katherine A.; Dudek, Jaclyn; Zhou, Zhi
Abstract: Real world places are important for foreign language (FL) learning since they provide rich and authentic language and cultural contexts for learners. However, numerous FL learners are unable to travel to target-language environments for language learning purposes. This article develops the concept of telepresence-place-based FL learning and examines its design principles through a mixed-method case study. Eleven adult English learners in China and four native-speaking English instructors participated in a series of learning activities at an arboretum on the campus of a university in the US. Based on the analysis of surveys, interviews, field notes, and learning activity videos, the findings show that using telepresence robots outside the classroom provides unique learning affordance for learners, especially when proper design principles are followed in designing the learning activities.